Hyaluronic acid/lysozyme self-assembled coacervate to promote cutaneous wound healing. (29th January 2020) - Zhao, Xiaoye; Wang, Lin; Gao, Jushan; Chen, Xi; Wang, Ke
Abstract : The preparation and wound healing in a full-thickness skin defect model of HL coacervate. Abstract : Traditional hydrogel dressings are limited in practical applications due to the complexity of the preparation and low biocompatibility. So, there is an urgent need to design wound dressing with simple preparation method, higher biocompatibility, and superior therapeutic effect. Additionally, using a polysaccharide/protein mixture system is an attractive method to prepare the gel. In this study, a simple mixture of hyaluronic acid/lysozyme (HL) was used to obtain the HL coacervate gel. HL coacervate has suitable viscoelasticity and excellent adhesion on the skin tissue. We demonstrated its highly efficient self-healing property to overcome fracture or deformation. HL coacervate showed a significant effect on promoting wound healing in a full-thickness skin defect model. Compared to the commercial 3M dressing, it has faster epithelial tissue regeneration and stronger collagen deposition. In addition, cytotoxicity and organ toxicity tests indicated its high safety. In summary, HL coacervate has broad clinical application prospects as a wound dressing material.